Pengaruh Pemberian Teknik Marmet Terhadap Produksi Asi Pada Ibu Post Partum Di Bpm Wilayah Kerja Puskesmas Sukorame Kota Kediri - Astri Dwi Ningrum; Ira Titisari; Finta Isti Kundarti; Arika Indah Setyarini (coba, 2017)
The decrease of breast milk production of postpartum mother in the early breast feeding process that become a problem for mother to provide breast milk early on her baby. Based on a preliminary study of the lowest exclusive breastfeeding rate coverage in the Kediri city is at Sukorame Public Health Center. This is because many postpartum mothers who felt less that give their milk formula or food other than breast milk in early lactation. The breast milk production could be stimulated by the use of intervention marmet technique. The purpose of this study was to investigate the influence of giving marmet technique to the breast milk production of the postpartum mother. This study is a quasi-experimental research design with post-test only control group design. The population in this study were all post partum mothers who met the inclusion criteria for the study in BPM working area of Sukorame Public Health Center Kediri City. The sampling technique is consecutive sampling with a sample of 26 respondents. Data collection was done by dividing into 2 groups: the experimental group and the control group and to assess the breast milk production using the observation sheet of breast milk production. Data analysis technique used is the Fisher Exact Test Test. The results obtained p value count (0.0074) < = (0.05) then H0 is rejected, meaning that there is the effect of giving marmet technique to the breast milk production. The conclusion of this study was the Marmet technique affects breast milk production of post partum mother. Giving Marmet technique can be applied to help the adequacy of breast milk production. Suggestions researchers is that all medical person can continue to support the improvement of service quality by taking into account maternal postpartum milk production that can impact the breastfeeding process. Keywords: marmet technique, breast milk production, post partum